If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -1(a + 8) = 1 Reorder the terms: -1(8 + a) = 1 (8 * -1 + a * -1) = 1 (-8 + -1a) = 1 Solving -8 + -1a = 1 Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '8' to each side of the equation. -8 + 8 + -1a = 1 + 8 Combine like terms: -8 + 8 = 0 0 + -1a = 1 + 8 -1a = 1 + 8 Combine like terms: 1 + 8 = 9 -1a = 9 Divide each side by '-1'. a = -9 Simplifying a = -9
| 3(r+2s)-3r= | | 3x=5x-4(x-3) | | 5x=y+3z | | 32+3x=-8(x+7) | | x=0.85x+0.1275 | | (3n-6)+n=42 | | 25y^2-4=0 | | 6x+7(y+x)= | | x^4+y^4=x^2+y^2 | | -10(h+5)-3=-83 | | (2a^2-a)+(2a-1)= | | 3y^2+10y+3=0 | | d^2-19d+28=0 | | 5+3(3a-8)=-91 | | A+b+a+c= | | -40=8b | | x+2x+y=828.50 | | 2(4-2m-3m)=3m-4m+2 | | lnx+ln(x+1)=7 | | 8w+5=-20 | | 3(5+2h)= | | 3j-20=10 | | 80(5x+8y)=499 | | 10x-5=-5x-5+15x | | 2x-(5x-8)+7=-8(6) | | x+.5=-1.3x-6.5 | | 4m+1=7-2m | | 13x-2x-4=40 | | 0=1-2x-4x^3 | | 5+3(n-4)=2n+1 | | -12=18-4w | | 3x-3=3/4(2x+12) |